Changes in the messenger RNA expression levels of Bcl‐2 family members and caspase‐8 and ‐3 in porcine ovarian follicles during follicular atresia. (21st September 2012) - Fu, Yanhui; Lin, Fei; Liu, Honglin
Abstract Follicular atresia is mainly modulated by the mitochondrial apoptotic pathway, which is regulated primarily by interactions between pro‐ and anti‐apoptotic genes at the mitochondrial level. The Bcl‐2 family members (e.g. Bak, Bax, Bid, Bim, Bcl‐xL, Bcl‐2 and Mcl‐1), caspase‐8 and ‐3 play a crucial role in the mitochondrial apoptotic pathway. In this study, we used single follicles to measure the messenger RNA (mRNA) expression levels of Bak, Bax, Bid, Bim, Bcl‐xL, Bcl‐2, Mcl‐1, caspase‐8 and caspase‐3 in healthy (H), early atretic (EA), and progressed atretic (PA) porcine follicles by quantitative real‐time RT‐PCR. Follicular atresia was assessed based on morphology and the ratio of progesterone to 17β‐estradiol. Our results indicate weak mRNA expression of Bim, Bid, Mcl‐1 and Bcl‐2 in the H group and significantly increased expression in the EA and PA groups (P < 0.01). The expression levels of Bak, caspase‐3 and Bcl‐xL were low in the H and EA groups and increased in the PA group (P < 0.01). Finally, the expression of Bax and caspase‐8 rose gradually with the progression of follicular atresia. Our findings indicate the mRNA expression levels of both pro‐apoptotic genes (Bak, Bax, Bid, Bim, caspase‐8 and caspase‐3) and anti‐apoptotic genes (Bcl‐xL, Bcl‐2 and Mcl‐1) were increased in the follicles during atresia in porcine ovaries. We propose that the increase in anti‐apoptotic gene transcription may prevent apoptosis by protecting against the effects of pro‐apoptotic gene expression. However, alterations in the balance of pro‐ and anti‐apoptotic gene expression may lead to follicular atresia.